Cargo systems in a translocal migrant community in la Mixteca Poblana - López Ángel, Gustavo (2020)
The governance system of indigenous communities differs from traditional notions, because unlike its passive condition, it rests on a constant exercise of transformation with dynamics derived from internal and international migration.  The traditional substantive citizenship has rested on a homogeneous conception of community, with unique membership systems, without repairing or including, in the analysis, the diversity of actors and processes that exist within it.  For this reason, the transition towards multicultural citizenship is one of the tasks ensuing the construction of public policies of the Mexican State.